Principles and Applications of Computer Graphics in Medicine - Vidal, F.P.; Bello, F.; Brodlie, K.W.; John, N.W.; Gould, D.; Phillips, R.; Avis, N.J. (Computer graphics forum, 2006)
The medical domain provides excellent opportunities for the application of computer graphics, visualization and virtual environments, with the potential to help improve healthcare and bring benefits to patients. This survey paper provides a comprehensive overview of the state‐of‐the‐art in this exciting field. It has been written from the perspective of both computer scientists and practising clinicians and documents past and current successes together with the challenges that lie ahead. The article begins with a description of the software algorithms and techniques that allow visualization of and interaction with medical data. Example applications from research projects and commercially available products are listed, including educational tools; diagnostic aids; virtual endoscopy; planning aids; guidance aids; skills training; computer augmented reality and use of high performance computing. The final section of the paper summarizes the current issues and looks ahead to future developments.